Preparation method of borate mineralized cerium-based rare earth polishing powder

Through the preparation method of borate mineralized cerium-based rare earth polishing powder, borate decomposition provides a semi-flow dynamic environment, solving the problems of high cost and poor grinding performance of cerium-based rare earth polishing powder, achieving high grain size and long The effect of service life.

CN119193004APending Publication Date: 2024-12-27GANSU RARE EARTH NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202411300225.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing preparation methods of cerium-based rare earth polishing powder have problems such as high cost, long production cycle, unstable product quality and degraded grinding performance, especially during high-temperature calcination, abnormal particles grow and structural defects are inevitable.

Method used

The preparation method of borate mineralized cerium-based rare earth polishing powder is adopted. Boric acid and fluorinating agent are added after ball milling of carbonate rare earth precursors, and aging and high-temperature calcination are carried out. The polishing powder is obtained by sieving and grading, and half of the borate is provided by decomposition of borate. The flow dynamic environment promotes solid phase reactions and improves unit cell strength and grinding accuracy.

Benefits of technology

The prepared cerium-based rare earth polishing powder has high grain size, low defects, good cutting ability and long service life, which reduces production costs, improves grinding accuracy and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193004A_ABST
    Figure CN119193004A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of borate mineralized cerium-based rare earth polishing powder, and belongs to the technical field of rare earth polishing materials. Comprising the following steps: adding water into a rare earth precursor for size mixing, then adding a fluorinating agent and a mineralizing agent for mixing, size mixing, ball-milling, aging, then carrying out spray drying to remove moisture, then carrying out high-temperature roasting, and screening the calcined material to obtain a polishing powder product. The operation process is stable and easy to implement, the average particle size of materials is adjusted through precursor ball milling, structural defects are eliminated, uniform dispersion of a fluorinating agent and a mineralizing agent is promoted, the mineralizing agent promotes a solid-phase reaction in the high-temperature roasting process, and therefore the solid-phase reaction temperature is reduced, and the unit cell agglomeration strength is enhanced; compared with a conventional production process, the cost of calcination and crushing grading is obviously reduced, and the prepared polishing powder has the advantages of strong grinding capability, good wear resistance, high grinding precision and high effective utilization rate compared with the existing product in the market, and can be used for rapid thinning of soft optical glass and surface precision machining of high-hardness and fragile glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth polishing materials, in particular to a method for preparing borate mineralized cerium-based rare earth polishing powder. Background Art

[0002] With the extension of the 5G industry and the rapid development of the optoelectronic field, the demand for grinding and processing of related components has increased dramatically. Among them, cerium-based rare earth polishing powder is widely used in the surface flattening and smoothness improvement of silicon-based materials such as glass substrates, optical electronic devices, and crystal jewelry due to its unique mechanical strength and chemical activity.

[0003] In recent years, key parameters such as display screen pixels, luminous materials, and touch acquisition rates have been updated and iterated at a high frequency. In order to effectively protect screen components, high-hardness panel glass represented by Apple's super-crystalline ceramic panel and Huawei Kunlun Glass has emerged in the market; in addition, in the fields of home appliance manufacturing, space reflectors, aerospace, space robots, and optical instruments, because optical components often need to be exposed to ultra-high and low temperatures, ultra-high and low pressures, low-expansion glass with ultra-low thermal expansion coefficients, denser structures, better electrical insulation and chemical stability is widely used. Typical brittle low-expansion optical glasses include Pyrex glass, quartz glass, and microcrystalline glass, such as BK7, Zerodur, and ULE. These high-hardness glasses can resist various scratches and abrasions, and also have excellent light transmission performance. Therefore, the industry's demand for fast, efficient, and ultra-high precision rare earth abrasive materials has increased dramatically.

[0004] Through the study of the effect of cerium-based rare earth polishing powder on silicon-based materials, it was found that the grinding process also has physical effects caused by the collision between the strong face-centered cubic CeO2 crystal cell aggregates and the surface of the silicon-based material. In addition, there is also Ce 3+ The chemical reaction of dehydration and dissociation of silanol bonds on the surface of silicon-based materials, the two effects complement each other and are defined as chemical mechanical polishing (CMP). 3+ / Ce 4+The proportion of trivalent cerium has become the focus of research on the improvement of cerium-based rare earth polishing powder. For example, the Chinese invention patent with patent publication number CN117487462A discloses a surface-modified cerium-based rare earth polishing powder with a high trivalent cerium content and a preparation method. The surface of the cerium-based rare earth polishing powder particles is modified by doping with praseodymium oxide and inorganic acids such as hydrochloric acid and nitric acid to increase the proportion of trivalent cerium, thereby increasing the polishing rate. However, the cost of praseodymium oxide is much higher than that of the highly abundant lanthanum cerium carbonate rare earth. The introduction of praseodymium oxide will greatly increase the cost of cerium-based rare earth polishing powder, and liquid inorganic acids are highly corrosive and volatile, which will cause the production process to be difficult to operate in a refined manner and increase the risk. Another example is the Chinese invention patent with patent publication number CN115321578A, which discloses a nano-spherical The invention discloses a fluorinated rare earth polishing powder and a preparation method thereof. The polishing powder precursor after sand grinding is fluorinated by using dispersants such as EDTA, citric acid and hydrofluoric acid, and an aging induction process is used to stabilize the crystal structure, and the surface area and pore structure of the particles are changed, so as to obtain a cerium-based rare earth polishing powder product with a high surface area and a stable crystal structure. However, the average particle size of the particles at the sand grinding end point of this method is 30 to 100 nm, which is difficult to achieve with conventional crushing means, and will greatly increase the production cycle and cost. Long-term sand grinding will cause wear of grinding media such as zirconium balls and steel balls, leading to the introduction of fine non-rare earth impurities, thereby affecting the product quality. Moreover, the aging induction process after sand grinding will cause new structural defects in the precursor, affecting the cell structure strength of the calcined product, and resulting in a decrease in the grinding performance of the polishing powder.

[0005] In addition, during the high-temperature calcination of the cerium-based rare earth polishing powder precursor, the solid-phase reaction between different rare earth oxide components is difficult. Generally, the reaction time is extended to make the reaction complete, or the calcination temperature is increased to accelerate the reaction rate. However, high-temperature calcination can easily cause abnormal growth of particles, affecting the grinding performance of the calcined product. Therefore, some suitable alkali metals or alkali metal halides with relatively low melting points and harmless to the product performance are selected and added to the reactants. The solvent melts at high temperature and can provide a semi-fluid environment, which is conducive to the diffusion of reactant ions and helps the product crystallization. Therefore, the selection of a suitable solvent is particularly critical to improving the grinding performance and service life of cerium-based rare earth polishing powder. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing borate mineralized cerium-based rare earth polishing powder, wherein the cerium-based rare earth polishing powder prepared by the method has fewer crystal cell defects, high particle agglomeration strength, high grain crystallization degree, better cutting ability, higher grinding accuracy and longer service life, thereby solving the problems raised in the above background technology.

[0007] The technical solution adopted by the present invention is as follows:

[0008] A method for preparing borate mineralized cerium-based rare earth polishing powder comprises the following steps:

[0009] Step 1: Select a rare earth carbonate precursor, add water to prepare the slurry, add a mineralizer and a fluorinating agent, stir, and obtain a rare earth fluoride slurry;

[0010] Step 2: ball milling the rare earth fluoride slurry obtained in step 1 to adjust the average particle size of the material, eliminate structural defects of the precursor, and promote the uniform mixing of the mineralizer and the fluorinating agent into the precursor;

[0011] Step 3: After aging, the ball-milled slurry obtained in step 2 is dehydrated to obtain a semi-oxide;

[0012] Step 4: calcining the semi-oxide obtained in step 3 at high temperature, and sieving and grading to obtain a polishing powder product.

[0013] Furthermore, in step one, the selected rare earth carbonate precursor is one of lanthanum cerium carbonate and lanthanum cerium semi-oxide, wherein the total amount of rare earth accounts for 40% to 80% of the precursor amount, and the mass fraction of the content of each rare earth element component is: the purity of cerium oxide (CeO2 / TREO) is 60% to 80%; the purity of lanthanum oxide (La2O3 / TREO) is 20% to 40%.

[0014] Furthermore, in step 1, the mineralizer is one or more of boric acid, sodium borate, and sodium tetraborate; the amount of the mineralizer added is BO3 3- / TREO mass fraction is calculated as 0.5% to 2.5%. In step 1, the fluorinating agent is one of hydrofluoric acid and rare earth fluoride; the amount of the fluorinating agent added is calculated as F - / TREO mass fraction is calculated as 4% to 8%.

[0015] Furthermore, in step 2, the final particle size D50 of the fluoride rare earth slurry after ball milling is 1.0 μm to 10 μm.

[0016] Furthermore, in step three, the aging time of the ball milled slurry is 2 to 6 hours.

[0017] Furthermore, in step three, the ball mill slurry is dehydrated by using a vacuum filtration machine and a drying oven, or a filter press and a flash quick dryer, or a spray dryer, and the low-temperature drying temperature is 130-400°C.

[0018] Furthermore, in step 4, the semi-oxide is calcined at a temperature of 850 to 970° C. for a time of 4 to 12 hours; the polishing powder product obtained by screening and grading has a particle size D50 of 1.0 to 8.0 μm and a maximum particle size D100 ≤ 75 μm.

[0019] The rare earth polishing powder component prepared by the method for preparing borate mineralized cerium-based rare earth polishing powder contains 91% to 96% rare earth oxide, 3.5% to 6.5% fluorine and 0.5% to 2.5% boron oxide by weight percentage.

[0020] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0021] 1. The present invention uses ball milling to pre-treat the precursor to an average particle size of 1.0 μm to 10 μm, which is easy to achieve using production ball milling equipment, and can eliminate structural defects left over from the precursor precipitation process, refine the precursor particle size, and allow the fluorinating agent and mineralizer to be more evenly dispersed in the precursor, thereby promoting the solid-phase reaction in the subsequent calcination process, allowing the unit cell to grow completely and have good structural strength, which is helpful to improve the grinding performance of the polishing powder. At the same time, the use of front-end mechanical ball milling to control the product particle size instead of crushing the calcined product can effectively control the production cost.

[0022] 2. The present invention introduces boric acid or sodium borate or sodium tetraborate as a mineralizer during the ball milling process of the precursor. The mineralizer is evenly mixed into the precursor carbonate after ball milling. During the high-temperature calcination process of the precursor, the borate decomposition product has a relatively low melting point and melts at high temperature, which can provide a semi-fluid environment for the solid phase reaction of the rare earth component in the polishing powder, which is conducive to the diffusion between the reactant ions and the crystallization of the product. The boron oxide is solid-dissolved in the cell gap, which plays a role in strengthening the cell agglomerates, improving the structural strength of the polishing powder, and extending the service life. At the same time, the addition of the mineralizer can reduce the temperature required for the nucleation and growth of the cerium-based rare earth polishing powder grains, thereby reducing the high-temperature calcination production cost.

[0023] 3. The preparation method of the cerium-based rare earth polishing powder provided by the present invention is easy to implement and has low production cost. The prepared polishing powder has better grinding ability and wear resistance than existing products on the market, and the effective utilization rate of the polishing powder is high. It can be used for rapid thinning of soft optical glass, and is also suitable for surface precision processing of high-hardness and brittle glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is an XRD schematic diagram of the rare earth polishing powder obtained in Example 1 of the present invention;

[0025] Figure 2 This is a SEM microscopic morphology image of the rare earth polishing powder obtained in Example 1 of the present invention;

[0026] Figure 3 This is a schematic diagram of XRD of the rare earth polishing powder obtained in Comparative Example 1;

[0027] Figure 4 This is a SEM microscopic morphology of the rare earth polishing powder obtained in Comparative Example 1;

[0028] Figure 5 These are the SEM images of the polishing powder samples after life tests of the boric acid mineralized polishing powder samples and the unmineralized polishing powder samples. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the drawings and specific data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0030] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.

[0032] In the embodiment of the present invention, a D8ADVANCEA25 X-ray diffractometer produced by Bruker Company of Germany is used to analyze the physical phase of the sample, with a copper target source, a ray wavelength λ=1.5406nm, and a scanning range of 0-80°; a SU8010 cold field emission scanning electron microscope produced by Hitachi Company of Japan is used to analyze the sample morphology; a Masters iser 2000 laser particle size analyzer produced by Malvern Company of the United Kingdom is used to analyze the sample particle size; a UNIPOL-802 automatic precision grinding and polishing machine is used to perform a grinding and polishing test; and a SuperViewW1 3D surface morphology profiler produced by Zhongtu Optics is used to measure the surface roughness of the glass substrate after grinding and polishing.

[0033] Example 1

[0034] This embodiment provides a method for preparing borate mineralized cerium-based rare earth polishing powder, comprising the following steps:

[0035] Take 4000g of lanthanum cerium carbonate rare earth precursor and add water to make slurry, then add 18.924g of boric acid according to 1.0% of the total amount of rare earth, and add 18.924g of boric acid according to the fluorine ratio (F - / TREO mass fraction) is 7.5%. Hydrofluoric acid is added to the slurry for fluorination. After stirring with an OS20~S overhead electric stirrer, zirconium balls are added as a medium in an XQM~10 planetary ball mill, and the slurry is ball-milled to an average particle size of 3μm. After aging for 2h, it is filtered with a SHZ~D(Ⅲ) circulating water multi-purpose vacuum pump, and the filter cake is dried at 300℃ for 8h in a LC~101~2B electric heating blast drying oven, and then calcined at 970℃ / 10h in a KSL~1200X muffle furnace to obtain a polishing powder sample. The XRD spectrum and SEM micromorphology of the obtained polishing powder product are shown in the figure. Figure 1 , 2 Show.

[0036] Example 2

[0037] Take 4000g of lanthanum cerium carbonate rare earth precursor and add water to make slurry, add 37.848g of boric acid according to 2.0% of the total amount of rare earth, and add 7.5% fluorine ratio (F - / TREO mass fraction) is added to the slurry for fluorination, and after stirring with an OS20~S overhead electric stirrer, zirconium balls are added as the medium in an XQM~10 planetary ball mill, and the slurry is ball-milled to an average particle size of 3μm. After aging for 2h, it is filtered with a SHZ~D(Ⅲ) circulating water multi-purpose vacuum pump, and the filter cake is dried at 300℃ for 8h in a LC~101~2B electric heating blast drying oven, and then calcined at 970℃ / 10h in a KSL~1200X muffle furnace to obtain a polishing powder sample.

[0038] Example 3

[0039] Take 4000g of lanthanum cerium carbonate rare earth precursor and add water to make slurry, add 18.924g of boric acid according to 1.0% of the total amount of rare earth, and add 7.5% fluorine ratio (F - / TREO mass fraction) is added to the slurry for fluorination, and after stirring with an OS20~S overhead electric stirrer, zirconium balls are added as the medium in an XQM~10 planetary ball mill, and the slurry is ball-milled to an average particle size of 8μm. After aging for 2h, it is filtered with a SHZ~D(Ⅲ) circulating water multi-purpose vacuum pump, and the filter cake is dried at 300℃ for 8h in a LC~101~2B electric blast drying oven, and then calcined at 970℃ / 10h in a KSL~1200X muffle furnace to obtain a polishing powder sample.

[0040] Example 4

[0041] Take 4000g of lanthanum cerium carbonate rare earth precursor and add water to make slurry, add 18.924g of boric acid according to 1.0% of the total amount of rare earth, and add 7.5% fluorine ratio (F - / TREO mass fraction) is added to the slurry for fluorination, and after stirring with an OS20~S overhead electric stirrer, zirconium balls are added as the medium in an XQM~10 planetary ball mill, and the slurry is ball-milled to an average particle size of 3μm. After aging for 2h, it is filtered with a SHZ~D(Ⅲ) circulating water multi-purpose vacuum pump, and the filter cake is dried at 300℃ for 8h in a LC~101~2B electric heating blast drying oven, and then calcined at 880℃ / 10h in a KSL~1200X muffle furnace to obtain a polishing powder sample.

[0042] Comparative Example 1

[0043] Take 4000g of lanthanum cerium carbonate rare earth precursor and add water to make slurry, and then add 7.5% fluorine ratio (F - / TREO mass fraction) was added to the slurry for fluorination, and zirconium balls were added as the medium in an XQM-10 planetary ball mill to grind the slurry to an average particle size of 3μm. After aging for 2h, the slurry was filtered with a SHZ-D (III) circulating water multi-purpose vacuum pump, and the filter cake was dried at 300℃ for 8h in a LC-101-2B electric heating blast drying oven, and then calcined at 970℃ / 10h in a KSL-1200X muffle furnace to obtain a polishing powder sample. The XRD spectrum and SEM micromorphology of the obtained sample are shown in Figure 3 , 4 Show.

[0044] The polishing powder samples obtained in the above embodiments and comparative examples were sieved and graded with a 200-mesh standard sieve. After the graded materials were added with additives and slurried at a solid-liquid ratio of 1:10, the powder cutting force test was carried out using a UNIPOL-802 automatic precision grinding and polishing machine. The test conditions were: Schott BF33 glass material, a feed peristaltic pump rate of 15 rpm, a grinding machine speed of 120 r / min, and the powder cutting force test results are shown in Table 1.

[0045] Table 1 Sample grinding test results

[0046] sample Cutting force (mg / min) Grinding surface roughness (nm) Example 1 1.100 0.485 Example 2 1.097 0.484 Example 3 1.067 0.512 Example 4 1.105 0.521 Comparative Example 1 0.833 0.543

[0047] It can be seen from the above table that the addition of boric acid can significantly improve the cutting ability of cerium-based rare earth polishing powder, and at the same time improve the roughness of the grinding surface. The mineralization effect of boric acid increases the agglomeration strength of the powder, and the agglomerates are not easy to break during the polishing process, which enhances the cutting ability of the powder. At the same time, after the introduction of boric acid, the single crystal cell size of the polishing powder is reduced, which helps to maintain the surface finish during the polishing process.

[0048] The UNIPOL-802 automatic precision grinding and polishing machine was used for the life comparison test. The test conditions were as follows: the graded samples were slurried with additives at a solid-liquid ratio of 1:10, the Schott BF33 glass material, the feed peristaltic pump rate was 15rpm, the grinding machine speed was 120r / min, and the glass substrate polishing amount (mg) and the center particle size (um) of the polishing powder slurry were continuously recorded within a 1-hour cycle. The trend is shown in Table 2. The powder cutting force test results and the SEM scanning electron microscopy results of the samples after the life test are shown in Table 2. Figure 5 Show.

[0049] Table 2 Sample life test results

[0050]

[0051] From the data in the above table, it can be seen that the addition of mineralizer can increase the polishing amount of cerium-based polishing powder per unit cycle, indicating that the powder has better cutting ability, and the particle size decreases slowly during the grinding process, indicating that the service life of the powder is greatly improved. At the same time, the surface roughness of the glass sample after grinding is lower, indicating that the powder has higher precision.

[0052] pass Figure 1 , Figure 3 From the comparison of XRD diffraction patterns, it can be seen that the polishing powder sample phases are mainly composed of CeO2 and LaOF phases, and the LaOF phase accounts for more than 40%. In addition, the introduction of boric acid will reduce the peak intensity of the characteristic peaks of CeO2 and LaOF, and the unit cell size will also be reduced, which is helpful to maintain the surface smoothness during the subsequent grinding process.

[0053] pass Figure 2 , Figure 4 From the comparison of SEM micromorphology, it can be seen that the addition of boric acid reduces the size of the polishing powder single crystal, and the unit cell agglomeration state is more compact, and the mineralizer melting phenomenon occurs between the unit cells, which makes the agglomerated particle structure stronger.

[0054] In summary, the cerium-based rare earth polishing powder sample prepared by the present invention has few unit cell growth defects and a high degree of crystallization. The introduction of the mineralizer can enhance the unit cell agglomeration strength, making it less likely to break during the polishing process. The powder cutting ability and wear resistance are enhanced. At the same time, the size of the single unit cell is reduced, and the polishing precision is better.

Claims

1. A method for preparing a borate mineralized cerium-based rare earth polishing powder, characterized in that: The following steps are included: Step 1: Select a rare earth carbonate precursor, add water to prepare the slurry, add a mineralizer and a fluorinating agent, stir, and obtain a rare earth fluoride slurry; Step 2: ball milling the rare earth fluoride slurry obtained in step 1 to adjust the average particle size of the material, eliminate structural defects of the precursor, and promote the uniform mixing of the mineralizer and the fluorinating agent into the precursor; Step 3: After aging, the ball-milled slurry obtained in step 2 is dehydrated to obtain a semi-oxide; Step 4: calcining the semi-oxide obtained in step 3 at high temperature, and sieving and grading to obtain a polishing powder product.

2. The method for preparing a borate mineralized cerium-based rare earth polishing powder according to claim 1, characterized in that: In step 1, the selected rare earth carbonate precursor is one of lanthanum cerium carbonate and lanthanum cerium semi-oxide, wherein the total amount of rare earth accounts for 40% to 80% of the precursor amount, and the mass fraction of the content of each rare earth element component is: the purity of cerium oxide is 60% to 80%; the purity of lanthanum oxide is 20% to 40%.

3. The method for preparing a borate mineralized cerium-based rare earth polishing powder according to claim 1, characterized in that: In step 1, the mineralizer is one or more of boric acid, sodium borate, and sodium tetraborate; the amount of the mineralizer added is calculated based on BO33- / TREO being 0.5% to 2.5%.

4. The method for preparing a borate mineralized cerium-based rare earth polishing powder according to claim 1, characterized in that: In step 1, the fluorinating agent is one of hydrofluoric acid and rare earth fluoride; the amount of the fluorinating agent added is - / TREO is calculated as 4% to 8%.

5. The method for preparing a borate mineralized cerium-based rare earth polishing powder according to claim 1, characterized in that: In step 2, the final particle size D50 of the fluoride rare earth slurry after ball milling is 1.0 μm to 10 μm.

6. The method for preparing a borate mineralized cerium-based rare earth polishing powder according to claim 1, characterized in that: In step 3, the ball mill slurry aging time is 2 to 6 hours.

7. The method for preparing a borate mineralized cerium-based rare earth polishing powder according to claim 1, characterized in that: In step three, the ball mill slurry is dehydrated by using a vacuum filtration machine and a drying oven, or a filter press and a flash quick dryer, or a spray dryer, and the low-temperature drying temperature is 130-400°C.

8. The method for preparing a borate mineralized cerium-based rare earth polishing powder according to claim 1, characterized in that: In step 4, the semi-oxide is calcined at a temperature of 850 to 970° C. for a time of 4 to 12 hours; the polishing powder product obtained by screening and grading has a particle size D50 of 1.0 to 8.0 μm and a maximum particle size D100 ≤ 75 μm.

9. The method for preparing a borate mineralized cerium-based rare earth polishing powder according to claim 1, characterized in that: In step 4, the components of the prepared rare earth polishing powder contain 91% to 96% rare earth oxide, 3.5% to 6.5% fluorine, and 0.5% to 2.5% boron oxide by weight.

Citation Information

Patent Citations

  • Nanometer sphere-like rare earth fluoride polishing powder and preparation method thereof

    CN115321578A

  • Surface-modified cerium-based rare earth polishing powder with high trivalent cerium content and preparation method of surface-modified cerium-based rare earth polishing powder

    CN117487462A

Cited By

  • Process for preparing rare earth polishing powder through temperature control precipitation method

    CN119979011A